Prediabetes and working memory in older adults. (October 2020) - Ennis, Gilda E.; Saelzler, Ursula; Umpierrez, Guillermo E.; Moffat, Scott D.
Insulin sensitivity, pancreatic β-cell function, fasting glucose, and 2-h post-load glucose were related to cognition in cognitively healthy nondiabetic older adults. Thirty-five adults (⩾65 years) underwent a 2-h oral glucose tolerance test and cognitive testing. Seventeen had normal glucose tolerance and 18 had intermediate hyperglycaemia or prediabetes (World Health Organization criteria). Fasting glucose and 2-h post-load glucose and oral glucose tolerance test–derived measures of β-cell function (oral disposition index) and insulin sensitivity were analysed as predictors of four cognitive domains: verbal episodic memory, verbal fluency, executive function, and working memory. The prediabetes group had significantly worse working memory performance than the normal glucose tolerance group. Controlling for age and education, decreased oral disposition index, and increased 2-h post-load glucose were significantly related to worse working memory performance. Prediabetes may worsen working memory in healthy older adults. Reduced pancreatic β-cell function should be investigated as a contributor to age-related cognitive decline.